2021
DOI: 10.1080/00224499.2021.1913567
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Within-Person Variability of Internal and External Sexual Consent

Abstract: Sexual consent is often conceptualized as an internal willingness to engage in sexual activity, which can be communicated externally to a sexual partner. Internal sexual consent comprises feelings of physical response, safety/comfort, arousal, agreement/want, and readiness; external sexual consent includes communication cues that may be explicit or implicit and verbal or nonverbal. Most previous research on sexual consent has focused on between-person differences; little attention has been devoted to examining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Together, these egalitarian aspects of the current vignette may have negated sex differences in consent perceptions that have been found in previous studies. Further, recent evidence suggests that gender’s association with sexual consent may be overshadowed when accounting for within-person differences such as type of sexual behavior (Willis et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, these egalitarian aspects of the current vignette may have negated sex differences in consent perceptions that have been found in previous studies. Further, recent evidence suggests that gender’s association with sexual consent may be overshadowed when accounting for within-person differences such as type of sexual behavior (Willis et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…We accounted for this nested design by testing the effects of within-person variables using a clustering option available in the lavaan package. This analytic approach allowed us to control for within-person variability, which previous research has indicated is relevant for sexual consent (Willis et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because people's experiences of internal sexual consent can vary from one encounter to the next (Willis et al, 2021b), researchers should consider collecting event-level contextual data to further understand the situational nuances of being willing to engage in sexual activity with another person. While we did not assess such characteristics in the present study, contexts in which sexual consent can vary include type of relationship with the sexual partner, gender of the sexual partner, type of sexual behavior, and whether substances were used.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Using data from a study designed to assess within-person variability of sexual consent ( Willis, Jozkowski, Bridges, Veilleux, & Davis, 2021 ), the purpose of this short communication was three-fold. First, we provided an updated account regarding whether the recall biases for alcohol use, sexual activity, and the co-occurrence of these behaviors are discrepant.…”
Section: Introductionmentioning
confidence: 99%